Enterprise Wide Systems: Universalistic or Contingent Solutions? - Marcela Porporato; Sandra Scott (STIE Malangkucecwara, 2014)
This paper explores whether the adoption of an enterprise wide system (EWS) is aligned with universalistic or contingent perspectives of management control system (MCS) design literature. It offers a schematic organization of the literature review on MCS design from a universalistic and contingent perspective. It considers recent adoptions of a well known EWS, discussing whether these adoptions exemplify a contingent or universalistic view of MCS. The evaluation of EWS adoptions is based on unstructured interviews with managers, EWS consultants and external accounting professionals. Interview findings suggest that although EWS are conceived as more flexible contingent systems, in practice they seem not to be. Interviewees highlighted the continuing tension between stakeholders who favour more contingent solutions (managers), and those who favour universalistic ones (consultants). The study contributes to the literature by organizing relevant work in the field around just two views of MCS (universalistic and contingent) to help to explain the alternatives a firm faces when adopting an EWS. Research conclusions must be considered preliminary as they are based on a limited sample of interviewees, identified through a snowball sampling technique. Next steps will involve larger samples, structured interviews and quantitative surveys within a longitudinal field study.